Race, equity, and public schools in post-apartheid South Africa: is opportunity equal for all kids? - Yamauchi, Futoshi (International Food Policy Research Institute, 2004)
This paper uses recently available South African school census data from 1996 and 2000 to assess variations in educational quality across former population groups of public schools and dynamic changes in post-apartheid South Africa. The author argues that unless the government actively strengthens its support to former Black schools in allocating both budget and personnel, a vicious cycle of poverty and low-quality education will persist. The worry is that children who do not receive a sufficiently high quality of education are less likely to engage in regular employment and are more likely to suffer from low wages, potentially contributing to the long-term poverty trap.